A Reaction to Critique from the Epistemological Sidelines - Garssen, Bart (Informal Logic, 2023)
In this paper, a reaction is presented to Siegel’s claim that the pragma-dialectical theory of argumentation ignores or neglects epistemological viewpoints that he finds vital to any normative theory of argumentation. The focus is on the most important problems in Siegel’s argument: 1) the ambiguity of the term ‘argument’ and the alleged negligence of this ambiguity in pragma-dialectics; 2) the critical rational perspective of the pragma-dialectical account; and 3) the alleged negligence of the “abstract propositional sense” of argument in pragma-dialectics.